Osobnost Józefa Piłsudského v polských učebnicích literatury - Michaela Zormanová (Studia Slavica)
The article aims to compare the image of Józef Piłsudski in Polish textbooks of literary education from the first grade to the last year of high school. Using discourse analysis, the article will offer metaphors, adjectives, images, historical context and concrete and abstract objects of living memory at the first, second and third levels of education.